Characterization of Bacterial Cellulose-Based Wound Dressing in Different Order Impregnation of Chitosan and Collagen - Khatarina Meldawati Pasaribu; Saharman Gea; Syafruddin Ilyas; Tamrin Tamrin; Izabela Radecka (Biomolecules, 2020)
Bacterial cellulose (BC), chitosan (Chi), and collagen (Col) are known as biopolymers which have met some properties that are required as wound dressing. This study focused on investigating the fabrication of BC-based wound dressing with chitosan and collagen, since chitosan has red blood cells binding and anti-bacterial properties, while collagen can support cell and tissue growth for skin wounds. The BC-based wound dressing was prepared by impregnating BC fibers in the chitosan and/or collagen solution for 24 h. FTIR was used to confirm the intermolecular interaction of amine and hydroxyl group of chitosan and/or collagen in BC-based wound dressing. Furthermore, the XRD diffractogram of the wound dressing show broader peaks at 14.2°, 16.6°, and 22.4° due to the presence of chitosan and collagen molecules in BC fibers. These results were then supported by SEM images which confirmed that chitosan and collagen were well penetrated into BC fibers. TGA curves revealed that BC/Chi/Col has better thermal properties based on the Tmax compare to BC/Col/Chi. Feasibility of the mats to be applied as wound dressing was also supported by other tests, i.e., water content, porosity, and hemocompatibility, which indicates that the wound dressing is classified as nonhemolytic materials. However, BC/Col/Chi was considered a more potential wound dressing to be applied compared to BC/Chi/Col since it has larger pores and showed better antibacterial properties (larger zones of inhibition) against S. aureus and E. coli via disk diffusion tests.